PENGARUH DAYA TARIK HUMOR DALAM IKLAN DI YOUTUBE TERHADAP BRAND IMAGE BUKA LAPAK - Josua Situmorang; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Advertisement with humor attraction are often become a popular ads. Ads with humor attraction are used for the purpose of attracting the audience, and making the recipient of the message become in a positive mood, so the probability of receiving messages is better and would be greater. This is used by Bukalapak, which is one of the biggest e-commerce companies in Indonesia, where they consistently used the humor attraction in every ads they have been made, it is considered good enough seen by the positive response from audiences and some of the awards that they get in the advertising. Advertisement represents the company as a media of communication, indirectly can create a perception about the company in audiences mind. This perception that will become an image or brand image. Brand image is the result of a consumer's view or judgment of a brand whether it is good or bad. This is become the underlying researcher, which want to know if there is an effect between the humor attraction in the advertisement of Bukalapak